KEABSAHAN DAN KEKUATAN PEMBUKTIAN TANDA TANGAN ELEKTRONIK YANG BELUM TERSERTIFIKASI - Intan Permata Ningrum (2022)
In Article 60 paragraph (2) of government regulations mention there are two types of Electronic Signatures, namely Electronic Signatures that are certified and have not been certified. Electronic signatures that have been certified are legal in force and have legal consequences. The purpose of writing this scientific research is to find out whether an electronic signature that has not been certified can be used and legally valid and how it stands before the law. The results of this study state that electronic signatures that have not been certified can be used and recognized by law as contained in Article 54 paragraph (1) of Government Regulation No. 82 of 2012. The strength of proofing an uncertified electronic signature is relatively weak because it does not have a safeguard that detects changes as well as a certified electronic signature.